HF-receiver Equipment for Frequency-and-Angular Sounding of the Ionosphere in Antarctica - I. Pikulik; S. Kashcheyev; V. Galushko; Yu. Yampolsky (Ukrainian Antarctic Journal, 2003)
The paper presents the structural diagram and design of the HF data-acquisition complex developed and manufactured at the Institute of Radio Astronomy for frequency-and-angular sounding of the ionosphere. The complex was deployed at the Ukrainian Antarctic station Akademik Vernadsky in February 2002 and has been operated during 12 month in the semi-automatic mode, monitoring traveling ionosphere disturbances. In particular, the processes of disturbance transfer from the near-surface atmospheric layers to the ionosphere and geospace heights were studied. This kind of monitoring has been organized for the first time in the aurora zone. It will greatly expand the possibility for the study of the lower-to-higher atmosphere integration in the Antarctic region and development of appropriate physical models.